2019
DOI: 10.1073/pnas.1900079116
|View full text |Cite|
|
Sign up to set email alerts
|

SLAMF9 regulates pDC homeostasis and function in health and disease

Abstract: SLAMF9 belongs to the conserved lymphocytic activation molecule family (SLAMF). Unlike other SLAMs, which have been extensively studied, the role of SLAMF9 in the immune system remained mostly unexplored. By generating CRISPR/Cas9 SLAMF9 knockout mice, we analyzed the role of this receptor in plasmacytoid dendritic cells (pDCs), which preferentially express the SLAMF9 transcript and protein. These cells display a unique capacity to produce type I IFN and bridge between innate and adaptive immune response. Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 66 publications
(61 reference statements)
0
21
0
Order By: Relevance
“…However, Sever et al also reported a relative decrease in the frequency of TNF-a-producing pDCs in CpG-stimulated lymph node cells from Slamf9 À/À mice with experimental autoimmune encephalomyelitis. 30 If optimal TNF-a production is dependent on SLAMF9 expression across multiple cell types, this may help to explain the impaired clearance of Salmonella in our studies.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, Sever et al also reported a relative decrease in the frequency of TNF-a-producing pDCs in CpG-stimulated lymph node cells from Slamf9 À/À mice with experimental autoimmune encephalomyelitis. 30 If optimal TNF-a production is dependent on SLAMF9 expression across multiple cell types, this may help to explain the impaired clearance of Salmonella in our studies.…”
Section: Discussionmentioning
confidence: 85%
“…The expression of SLAMF9 by pDCs was corroborated by recent literature. 30 Among CD11b + cells, weak expression of SLAMF9 is found in CD11c high conventional DCs, whereas highest expression of SLAMF9 in myeloid cells was found among a fraction of CD11c low cells corresponding to the Ly6Cmonocyte subset observed in blood (Fig. 3g).…”
Section: Mouse Slamf9 Has Restricted Expression Among Antigen-presentmentioning
confidence: 92%
“…pDC stimulation through TLR7/8/9 triggers production of high levels of IFNα which orchestrates global anti-viral responses across nearly all cell types [28]. It has been shown recently that SLAMF9 signaling contributes to proper migration and function of pDCs [29], indicating a potential role for SLAMF9 in pDC-mediated antiviral responses. Following the acute phase of HIV infection, plasma viremia drops significantly, and circulating CD4 + T cell levels return to normal levels.…”
Section: Immune Responses To Viral Infectionsmentioning
confidence: 99%
“…Regulation of macrophage and pDC responses [21,29] Monocytes, pDCs, DCs, T cells, B cells, macrophages.…”
Section: Slamf9 (Sf2001 Cd84h1)mentioning
confidence: 99%
See 1 more Smart Citation